A new coumaronochromone and a new alkanoyl-dihydrofuranoflavone glycoside from Eriosema robustum (Fabaceae). (October 2018) - Awouafack, Maurice Ducret; Wong, Chin Piow; Tane, Pierre; Morita, Hiroyuki
Graphical abstract: Highlights: The phytochemicals of a medicinal plant, Eriosema robustum, were re-investigated. A new coumaronochromone (1 ) and a new furanoflavone (2 ) were isolated from the plant. The structures of1 and2 were characterized by NMR and HR-ESIMS. 1 and2 exhibited weak activity with MICs > 150 μg/mL against bacteria and fungi. 1 (IC50 340.3 ± 0.1 μM) and2 (IC50 524.6 ± 0.1 μM) had weak antioxidant activity. Abstract: A new coumaronochromone, eriocoumaronochromone (1 ), and a new alkanoyl-dihydrofuranoflavone glycoside, robusflavone C (2 ), as well as seven known compounds, 6-prenylpinocembrin (3 ), desmoxyphyllin A (4 ), prutin (5 ), genistein (6 ), vitexin (7 ), kaempferol (8 ), and p -hydroxy benzoic acid (9 ), were obtained after phytochemical re-investigation of the EtOAc-soluble portion from the EtOH extract of the twigs of Eriosema robustum . The structures of the new compounds were elucidated by analyses of their spectroscopic data (1D- and 2D- NMR, and HR-ESIMS) and chemical conversion.1 and2 exhibited weak antioxidant activity with IC50 340.3 ± 0.1 and 524.6 ± 0.1 μM in 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical assay, and possessed weak antimicrobial activity with MICs > 150 μg/mL against Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli, Candida albicans, and Saccharomyces cerevisiae .